O desenho nos livros didáticos de matemática em braile: a geometria e o desenho geométrico para alunos com deficiência visual - Moreira, Soane da Silva (2017)
The purpose of the research was to analyze the chapters of Geometry and Geometric Drawing of Mathematics textbooks of elementary education written in braille, to understand how teaching and learning of the blind students is processed. I showed the Drawing as a school subject in parallel with the analysis of the textbooks of Mathematics in Braille, as an empirical basis, specifically the chapters directed to Geometry, those that deal with geometric forms. I focused on concepts such as accessibility to education, special education, specialized educational care, in / exclusion and mental image. I highlighted the data of the identified publishers and authors, and then carry out their investigation. I used a qualitative approach, with informal conversations with the direction and with some teachers of the Pedagogical Support Center and the Integrated Center of Municipal Education Professor Joselito Falcão de Amorim on the students with visual deficiency that study in each place, the materials to which could have access in each institution, the methodologies used and other topics that have arisen in relation to my research. The subjects involved were seven visually impaired students who study at a public school in the city of Feira de Santana, the Integrated Education Center of Professor Joselito Falcão de Amorim, and that participate in the specialized educational service in the multifunctional resource room, at the same place. Documentary analyzes and semi-structured interviews were done. The mental images already constructed by blind students and life experiences are valuable supports in this educational process. The results show that the geometric forms present in the textbooks of Mathematics in Braille help a lot in the teaching / learning of Geometry / Geometric Drawing, and that the joint study is able to develop the student in an interdisciplinary way. Students with visual impairment can perceive the geometric shapes by touch and they are able to acquire new knowledge through other senses, but there are some geometric figures worked on these books that alone can not make this happen, being necessary the use of others educational resources that aim to represent these figures in a more concrete way.